Bioavailability of plant sterol-enriched milk-based fruit beverages: In vivo and in vitro studies. (April 2015) - Garcia-Llatas, Guadalupe; Cilla, Antonio; Alegría, Amparo; Lagarda, María Jesús
Highlights: Comparison of in vivo and in vitro effects of plant sterol-enriched beverages. No influence of coexistence of plant sterols and β-cryptoxanthin on phytosterolemia. Significant increase of sitosterol and campesterol serum levels after in vivo study. Abstract: This study for the first time compares the in vivo (response in serum from individuals of an interventional study) and in vitro effects (bioaccessibility determined from simulated gastrointestinal digestion) of two plant sterol (PS)-enriched milk-based fruit beverages (with and without tangerine fruit juice rich in β-cryptoxanthin (β-Cx)) in order to assess their suitability as PS-enriched food matrixes, and the possible interactions between the two bioactive compounds (β-Cx and PS) that might affect their absorption. The randomized, double-blind, crossover study (performed in 36 postmenopausal women) showed the β-sitosterol and campesterol serum concentrations after four weeks of consumption of the beverages (1.5 g PS/day) to increase significantly (ranging 1.6–2.4 µg/mL and 0.3–0.4 µg/mL, respectively), thereby confirming suitability as matrices for PS-enrichment. The results therefore indicated similar behavior of PS supplied by these beverages and evaluated through in vitro or in vivo assays, independently of whether the samples contained β-Cx or not.